Profil Fitokimia, Aktivitas Antioksidan, Total Flavonoid, Total Fenolik, dan Total Tanin Ekstrak Bunga Tapak Dara - Mizan Sahroni; Nina Artika Dewi; Najwa Afifah; Yulianty Yulianty (Program Studi S1 Farmasi, STIKES Senior, Medan, 2026)
The use of plants in medicine has been practiced since prehistoric times and continues to develop as a safer and more economical alternative to modern therapies. Catharanthus roseus L. is a tropical plant commonly found in Indonesia, known for its diverse pharmacological benefits. This study aims to identify the phytochemical profile, total flavonoid content, total phenolic content, total tannin content, and antioxidant activity of Catharanthus roseus flower extract. Extraction was carried out by maceration using absolute ethanol, followed by phytochemical screening and UV-Vis spectrophotometric analysis of bioactive compounds. Phytochemical screening revealed the presence of flavonoids, phenolics, and tannins (strong positive reaction), and alkaloids (positive), while saponins, steroids, and terpenoids were not detected. Quantitative analysis showed total flavonoids of 17.92 mgQE/g, total phenolics of 24.53 mgGAE/g, and total tannins of 38.27 mgTAE/g. Antioxidant activity assay using the DPPH method indicated an IC₅₀ value of 502.89 µg/mL, which falls under the weak category. Nevertheless, the high content of polyphenolic compounds supports the potential of the flower extract as a natural antioxidant source. This study provides scientific evidence for the future development of C. roseus as a phytopharmaceutical agent and encourages further exploration of advanced extraction techniques to enhance its bioactivity. Keywords: Antioksidant, Catharanthus roseus, Flavonoid, Phenolic, Tanin.